Oxygenate-mediated catalysis for CO2 hydrogenation: A sustainable path to light olefins - Fatemeh Biabangard; Jafar Towfighi Darian; Masoud Safari Yazd (Journal of CO2 Utilization)
The hydrogenation of CO2 to light olefins using renewable hydrogen presents a promising strategy for mitigating greenhouse gas emissions and addressing the growing demand for sustainable industrial chemicals. This review focuses on the oxygenate-mediated species involved in the CO2 conversion route, a highly selective and efficient alternative to traditional Fischer-Tropsch synthesis. Central to this process are bifunctional catalysts, which integrate metal oxides for CO2 activation and zeolites for hydrocarbon formation, enabling tandem catalysis. Key catalyst components, such as ZnO, Cu, ZrO2, and In2O3, play critical roles in CO2 adsorption, stabilization of intermediates like methanol, methoxy, and ketene, and their subsequent conversion into light olefins via distinct pathways, including the ketene, formate, and dimethyl ether (DME) routes. Advances in catalyst design, encompassing morphology, active site proximity, and surface modification, alongside the optimization of operating conditions such as temperature, pressure, and space velocity, have significantly enhanced catalytic efficiency and product selectivity. Furthermore, innovations in zeolite frameworks like SAPO-34, with their shape-selective properties, have contributed to minimizing by-products and maximizing olefin yield. This comprehensive analysis provides insights into the factors influencing catalytic performance, emphasizing the need for interdisciplinary research to overcome challenges such as catalyst deactivation and scalability. By integrating advanced catalyst designs with optimized process parameters, this study outlines a roadmap for sustainable CO2-to-olefin conversion, contributing to environmental protection and a circular carbon economy.